GE_GERICHTE P/2511/2012 vom 28. Juni 2013 - GE Cour de justice (2013)
DÉFENSE D'OFFICE; FIXATION DE LA PEINE; ATTÉNUATION DE LA PEINE; PLAIGNANT; DÉPENS | CPP.132.1.b; CP.48.1.c; CO.47; CPP.433.1.a; CPP.124.2